Emosional Konsumen Sebagai Intervening Pengaruh Konten Pemasaran, Electronic Word Of Mouth, dan Pada Niat Beli Di Aplikasi Tiktok - Anas, M Yusuf Azwar; Senjani, Nurrohmah (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2023)
The research objective is to explain and analyze marketing content, electronic word of mouth (EWOM), and live broadcasts on purchase intentions through consumer emotions as intervening variables in the TikTok application. The quantitative method was analyzed using SmartPLS version 4.0.9.4 with the SEM (Structural Equation Modeling) analysis method. This research involved 119 respondents. The results of the analysis explain that content marketing has no effect on consumer emotions, EWOM has an effect on consumers' emotions, and live broadcasts have an effect on consumers' emotions. Marketing content has no effect on purchase intention. EWOM influences purchase intention, and live broadcast influences purchase intention. EWOM marketing content and live broadcasts have no effect on consumer emotional purchase intentions in the TikTok application